Bacteriophage Infectivity Against Pseudomonas aeruginosa in Saline Conditions - Scarascia, Giantommaso; Yap, Scott A.; Kaksonen, Anna H.; Hong, Pei-Ying (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa is a ubiquitous member of marine biofilm, and reduces thiosulfate to produce toxic hydrogen sulfide gas. In this study, lytic bacteriophages of Podoviridae family were isolated and applied to inhibit the growth of P. aeruginosa in planktonic mode at different temperature, pH and salinity. Bacteriophages showed optimal infectivity at a multiplicity of infection of 10 in saline conditions, and demonstrated lytic abilities over all tested temperature (25, 30, 37 and 45 oC) and pH 6 to 9. Planktonic P. aeruginosa exhibited significantly longer lag phase and lower specific growth rates upon exposure to bacteriophages. Bacteriophages were subsequently applied to P. aeruginosa-enriched biofilm and were determined to lower the relative abundance of Pseudomonas-related taxa from 0.17-5.58% in controls to 0.01-0.61% in treated microbial communities. The relative abundance of Alphaproteobacteria, Pseudoalteromonas and Planococcaceae decreased, possibly due to the phage-induced disruption of the biofilm matrix. Lastly, when applied to mitigate biofouling of ultrafiltration membranes, bacteriophages were determined to reduce the transmembrane pressure increase by 18% when utilized alone, and by 49% when used in combination with citric acid. Collectively, the findings demonstrated that bacteriophages can be used as a biocidal agent to mitigate undesirable P. aeruginosa-associated problems in seawater applications.